(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
The COVID-19 pandemic has led to a new era where applied learning has to go virtual. This hastened the need for students to be equipped with virtual skillsets, including the ability to manage 3-D augmented reality tools for future work. This paper introduces the virtual art platform as a means to prepare students for the new world, which requires a multidisciplinary approach to solving problems and digital skills to work within the virtual environment. The paper will examine the multidisciplinary practice and perspectives involved in setting up the virtual art gallery, introduce features of Virtual Art Gallery platforms and finally consider the potential benefits of using these platforms for the student’s professional careers.